2011
DOI: 10.4319/lo.2011.56.1.0394
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurements of root growth and productivity in the seagrasses Posidonia australis and P. sinuosa

Abstract: The effects of nutrients and planting season on root growth were investigated in transplants of the seagrasses Posidonia australis and P. sinuosa. Difficulties with sampling and estimating root growth of these submerged plants were overcome by growing transplants, with all roots removed initially, in pots containing a standardized sand medium. Nitrogen (N), phosphorus (P), and nitrogen and phosphorus combined (N + P) were added to pots. Root elongation and productivity were measured after harvesting at 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
0
14
1
Order By: Relevance
“…2), suggesting that other factors affecting aboveground biomass may be confounding clear responses to nutrient additions. This is supported by Hovey et al (2011), who demonstrated decreased root productivity with N additions in summer, which is a typical response when nutrients in the sediment are at adequate to saturating levels (Short 1987).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…2), suggesting that other factors affecting aboveground biomass may be confounding clear responses to nutrient additions. This is supported by Hovey et al (2011), who demonstrated decreased root productivity with N additions in summer, which is a typical response when nutrients in the sediment are at adequate to saturating levels (Short 1987).…”
Section: Discussionmentioning
confidence: 69%
“…Porewater concentrations taken from inside the pots showed that nutrients were released from Osmocote fertiliser with concentrations up to 5 times higher than controls at ambient nutrient levels (Table 1). Nutrient concentrations in leaves and rhizomes were also higher when N or P was added, evidence that plants were taking up the nutrients (see Hovey et al 2011 for plant nutrient concentrations). No significant change in shoot to root ratio was detected, but it was highly variable (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Mediterranean Sea, Posidonia oceanica (P. oceanica) represents the most important seagrass in terms of productivity, distribution and habitat structuring. It provides substratum to a species-rich epiphytic community [12,13], which achieves maximum biomass between the end of spring and the end of summer [1,14]. Monitoring of epiphyte of P. oceanica beds is becoming a useful tool to test the health of coastal environment and several countries have developed programs to study the distribution and the characteristics of seagrass beds and their epiphyte [1,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%